2012
DOI: 10.1111/j.1365-2486.2012.02788.x
|View full text |Cite
|
Sign up to set email alerts
|

Traditional shifting agriculture: tracking forest carbon stock and biodiversity through time in western Panama

Abstract: Reducing Emissions from Deforestation and forest Degradation (REDD+) requires developing countries to quantify green-house gas emissions and removals from forests in a manner that is robust, transparent, and as accurate as possible. While shifting cultivation is a dominant practice in several developing countries, there is still very limited information available on how to monitor this land-use practice for REDD+ as little is known about the areas of shifting cultivation or the net carbon balance. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 65 publications
(98 reference statements)
5
20
0
Order By: Relevance
“…Above-ground biomass for the study area is at the lower end of the scale, as a result of the fact that the area has been impacted by human uses like agriculture and cattle ranching at least since Mexico's colonial era and heavily used for shifting cultivation over the last fifty years. Our results agree with other reports that above-ground carbon stocks increase rapidly in the years following cultivation, the early forest successional stages (Read and Lawrence 2003;Chazdon et al 2007;Lebrija-Trejos et al 2010;Williams-Linera et al 2011;Pelletier et al 2012). Where the fallow phase is long, the carbon stocks would reach levels similar to those of old growth forests after 20 years, although more of this carbon is in the soil and less in the above-ground pools.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Above-ground biomass for the study area is at the lower end of the scale, as a result of the fact that the area has been impacted by human uses like agriculture and cattle ranching at least since Mexico's colonial era and heavily used for shifting cultivation over the last fifty years. Our results agree with other reports that above-ground carbon stocks increase rapidly in the years following cultivation, the early forest successional stages (Read and Lawrence 2003;Chazdon et al 2007;Lebrija-Trejos et al 2010;Williams-Linera et al 2011;Pelletier et al 2012). Where the fallow phase is long, the carbon stocks would reach levels similar to those of old growth forests after 20 years, although more of this carbon is in the soil and less in the above-ground pools.…”
Section: Discussionsupporting
confidence: 91%
“…Hence, continuous "harvesting" of the trees, such that the average tree population remains youthful, may result in higher average annual uptake of carbon. Recent research in humid tropical forests (rainforest in the Maya region of Central America, Amazon and Panama) has suggested that shifting cultivation is much less damaging to carbon stocks than had been earlier thought (Pelletier et al 2012;Nigh and Diemont 2013). Whether the new plot is cut in previously un-touched (primary) forest or in a secondary forest may, however, have important consequences for CO 2 emissions and carbon sequestration (Detwiler and Hall 1988;Fukushima et al 2008;Lawrence et al 2010).…”
Section: Carbon Stocks In Shifting Cultivation Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…If future demand for agricultural crops exceeds the yield of the traditional agricultural activities, agricultural intensification will become a necessity. This intensification could eventually require less land than currently to sustain the local population 33,34 , thereby securing the remaining forest and its carbon stock. However, the choice of agricultural system will critically affect the carbon balance.…”
Section: Discussionmentioning
confidence: 99%
“…Determining the proximate and underlying causes of deforestation and forest cultivation in rainforests where clearings are on average + 2 ha (Pelletier et al, 2012).…”
mentioning
confidence: 99%